Study of IL-33 and IL-1R4 in Iraqi Rheumatoid Arthritis Female Patient's with and without Dyslipidemia Prone to Atherosclerosis - Nazar, Lara Ali; Abass, Eiman AA.` (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
This study is planned to find relationship between interleukin-33 (IL-33) with its receptor interleukin-1 receptor 4 (IL-1R4), and assurance IL-33/IL-1R4 proportion as biomarker to atherosclerosisin rheumatoid arthritis (RA) Iraqi females patients with and without dyslipidemia. This study was attempted at Baghdad Teaching Hospital included 60 females patients with RA that were isolated into: 30 patients with dyslipidemia(G2), 30 patients without dyslipidemia(G3) and 30 individual as control group (G1) .Patients were experiencing treatment by methortexiene medication, analyzed by rheumatoid factor(RF) and erythrocyte sedimentation rate( ESR) tests. All patients and control groups age ranged from (30-55) years. The results show an increase in ESR, RF, IL-33, and IL-1R4 levels. In addition to decrease in IL-33/IL-1R4 ratio in the two patients groups when contrasted and control group. The momentum examine inferred that the level of ESR, and  IL-33 in RA Iraqi females  patients with dyslipidemia were higher than that in RA Iraqi females patients without dyslipidemia, while the level of IL-33/IL-1R4 ratio in RA Iraqi females patients with dyslipidemia was lower than that in RA Iraqi females patients without dyslipidemia patients; in this manner the IL-33/IL-1R4 ratio may be used as a biomarker in diagnostic early porn to atherosclerosis in RA females patients with dyslipidemia